Docência: conexões, resistências e algumas histórias - Veríssimo, Cátia Aparecida (2016)
The objective in this research consisted in verify possible relations between the teaching work and the negative and positive impacts on personal and professional life of teachers from municipal and state public network in a city in Minas Gerais. The International Labour Organization (ILO), in 1983, already pointed teachers as the second professional category worldwide suffering with diseases of occupational character. So, it is justified the study considering the immeasurable social importance of this professional class, since by means it the individuals are constituted and establish their relationship with knowledge and society. In the study initially was adopted exploratory nature, it was used qualitative approach and data were collected in questionnaire form and semistructured interview being evaluated and treated from the content analysis; the sample was composed of responses of the three teachers. It was found that many are the challenges faced by teachers, among many, they highlighted precarious work, gender relations, violence and insufficient training, these factors imply in different costs that directly impact the health of workers, resulting in illnesses, move away for awhile, lack of motivation and career withdrawal. On the other hand, the teachers interviewed revealed that the affection relationship established with the students have become important motivational source associated to their needs of work and remain financially.